The influence of professional mission on the professional quality of college teachers: The intermediary role of job burnout and the regulating role of social support - Zhen, Mo; Liu, Qian (Nurture, 2024)
Purpose: This study seeks to explore the influence of a professional mission on university teachers specifically examining the mediating role of job burnout and the moderating impact of social support. Design/Methodology/Approach: Data from university teachers were collected for this study using a questionnaire survey method and the results were carefully analysed using the relevant statistical techniques. Findings: The study finds a positive relationship between a strong professional mission and high professional quality in university teachers. Job burnout and social support serve as intermediaries and regulators. Increased burnout weakens the mission’s influence while reduced burnout correlates with enhanced professional quality. A strong social network enhances a professional mission’s beneficial effects. Conclusion: This study explores the relationship between a professional mission and university professors highlighting the mediating effects of social support and job burnout. The findings offer valuable insights for improving educational quality and supporting teachers’ personal growth. This research significantly contributes to understanding key factors in the career development of college teachers, providing enlightening perspectives for educators and policymakers. Limitations/Significance: This study ignores personal variables in favour of examining only the effects of professional missions on university teachers’ professional development. Observations and interviews are two unique methodologies that are necessary for a thorough understanding relying solely on surveys may introduce subjectivity. Practical Significance: Findings guide institutions and policymakers to boost education quality by supporting teachers’ professional development through training and social support and addressing burnout. Contributions to the Literature: The study fills gaps by confirming the beneficial influence of professional missions on the careers of teachers and guiding the improvement of education.